High H2O2 Utilization Promotes Selective Oxidation of Methane to Methanol at Low Temperature - Yan, Yang; Chen, Changlei; Zou, Shihui; Liu, Juanjuan; Xiao, Liping; Fan, Jie (Frontiers in Chemistry, 2020)
Selective oxidation of methane to methanol has been often considered as a “holy grail” reaction in catalysis. Herein, we systematically investigate the effect of solution pH and Pd-to-Au ratio of AuPdx colloid on the catalytic performance of methane oxidation. It is revealed that these two parameters can determine the amount of H2O2 participated in the reaction, which is linearly related to the productivity of oxygenates. A high catalytic performance in methane activation requires a high utilization of H2O2 to generate more ·OH. The optimal pH is 3.0 and the optimal Pd-to-Au ratio is between 0.1 to 0.7.